GSTM1 and GSTT1 null polymorphisms in elite Portuguese swimmers - Dias, A. F.; Costa, A. M.; Ramalhinho, A.; Breitenfeld, L. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Glutathione S-Transferases are a superfamily of ubiquitous multifactorial enzymes, which play a key role in cellular detoxification, protecting macromolecules from attack by reactive electrophiles, including reactive oxygen species (ROS) and chemotherapeutic agents. GSTs are the most abundant intracellular enzymes, and have multiples roles as anti-oxidant enzyme (Ramalhinho et al., 2011). The purpose of this study was to examine the association between the GSTM1 and GSTT1 null polymorphisms and event expertise in elite Portuguese swimmers. After informed consent, a group of elite swimmers (n=33, 20 males and 13 female, 18.84 + 2.97 years), designated as Olympic candidates, were recruited. The swimmers were stratified into two groups, based on their current distance event of expertise (Costa et al., 2009): short distance swimmers, between 50 and 200 m (mainly anaerobic events) and middle distance swimmers, between 400 and 1.500 m (mixed anaerobic and aerobic events). A control group of healthy individuals (n=52, 38 males and 14 females, 20.5+1.52 years) was also selected from the Portuguese population (college students), with no background in swimming. Genomic DNA was extracted from blood samples, and genotyping analyses were performed by PCR methods. Odds ratios (ORs) and 95% confidence intervals were calculated. The results showed that the presence of GSTT1 protein (in the absence of GSTM1 protein) seems to be important for both short distance (p=0.048) and middle distance swimmers (p=0.048) when compared with the controls (GSTT1 present + GSTM1 null: 22.8% for controls; 27.0% for short distance swimmers, and 18.0% for middle distance swimmers). The genotype distribution by gender showed that the presence of the GSTM1 protein alone appears to be relevant female middle distance performance (GSTM1 present: 15.4% for controls and 12.0% for middle distance female swimmers, p=0.020). The results seem to support an association between the presence of the GSTT1 protein and athletic performance in both genders. However, the GSTM1 null polymorphism seems to confer some advantageous characteristics to female swimmers for middle distance swimming performance.